Pengaruh Struktur Kepemilikan Terhadap Kinerja Perusahaan Dimoderasi Oleh Karakteristik Dewan Komisaris - Ilham Maulana; Muhammad Alkirom Wildan; Nurita Andriani (Jurnal Akuntansi, 2021)
This study was conducted to examine the effect of proxied ownership structure using institutional ownership, foreign ownership and managerial ownership variables which are moderated by the characteristics of the board of commissioners as proxied by the size of the board of commissioners, and the proportion of independent board of commissioners on company performance as measured by the firm's financial performance. Proxied by return on assets and return on equity and firm value proxied by Tobin's Q and market to book ratio. With a total of 81 samples from financial service companies listed on the IDX in 2018 tested using WarpPLS 7.0, the researchers found that ownership structure has a negative effect on financial performance and firm value, the characteristics of the board of commissioners have a positive effect on financial performance and firm value, and only interaction characteristics the board of commissioners in the relationship between ownership structure and financial performance which can be a moderating variable. Keywords: Ownership Structure, Firm Performance, and Characteristics of The Board of Commissioners.